2005
DOI: 10.1007/s10804-005-2486-4
|View full text |Cite
|
Sign up to set email alerts
|

Prehistory of Native Americans on the Central American Land Bridge: Colonization, Dispersal, and Divergence

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.Springer is collaborating with JSTOR to digitize, preserve and extend access to Journal of Archaeological Research. STOR

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
1
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(72 citation statements)
references
References 147 publications
3
64
1
4
Order By: Relevance
“…We now propose that all bone and shell formerly identified in D4 is intrusive. Therefore, contrary to earlier reports Ranere, 1984, 1992 a-c), we can no longer argue on the basis of the Vampiros shelter data that coastal resources were exploited in Pacific Panama during the Paleoindian and Early Preceramic periods (i.e, 11,500-7000 BP) Cooke, 2005). (Of course, coastal sites belonging to this period may be submerged).…”
Section: Wasps Crabs Iguanas and Rodents Burrow Into Thecontrasting
confidence: 76%
See 3 more Smart Citations
“…We now propose that all bone and shell formerly identified in D4 is intrusive. Therefore, contrary to earlier reports Ranere, 1984, 1992 a-c), we can no longer argue on the basis of the Vampiros shelter data that coastal resources were exploited in Pacific Panama during the Paleoindian and Early Preceramic periods (i.e, 11,500-7000 BP) Cooke, 2005). (Of course, coastal sites belonging to this period may be submerged).…”
Section: Wasps Crabs Iguanas and Rodents Burrow Into Thecontrasting
confidence: 76%
“…Subsequent research has shown that the early coastal sites of Parita Bay were in fact coeval with and culturally related to many other small settlements dispersed across both watersheds of central Panama (Cooke, 2005;Cooke and Ranere, 1992a,b,c;Griggs, 2005). Multi-proxy analyses of lake sediments at La Yeguada (see Figure 1b) show that people were felling and burning forests in the Pacific foothills and plains at this time (summarized in Piperno and Pearsall, 1998: 175-179).…”
Section: Cultural and Geological Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…and squash (Cucurbita) -were being widely planted in Panama by the Late Preceramic period of 7000e4500 BP (Piperno et al, 2000a(Piperno et al, , 2000bDickau et al, 2007). The use of fire and clearance of vegetation for agriculture related to permanent settlements is evident in highland western Panama, near the Barú volcano, after~2860 BP (Behling, 2000;Cooke, 2005).…”
Section: The Role and Timing Of Barú Eruptions During Human Occupationmentioning
confidence: 99%